Transportation synergies in inbound logistics flow at automotive assembler plant - Ferreira, J.; Martins, A. (22nd International Symposium on Logistics (ISL 2017), 2017)
Transportation costs are responsible for a large portion of the logistics cost. This is particularly important in companies that are located in peripheral countries. Valuable cargo companies under these conditions tend to receive more often, which easily leads to LTL. The purpose of this paper is to assess alternative scenarios for reduction of transportation cost for a car assembler in Iberia, taking into account the development of a collaborative software to handle sharing process at low prices and risks, attempting a somewhat flexible solution in a rigid industry. The proposed approach looks for logistic data flows and identifies aggregation solutions for inbound flows using rail solution and sharing space with other players to balance outbound traffic.